The two way relationship between diabetes mellitus and periodontal disease - Ongko, Darius Pranajaya; Chuan, How Kim; Halim, Susanna (Jurnal Prima Medika Sains, 2025)
Periodontitis and diabetes mellitus are common chronic diseases with an established bidirectional relationships. Epidemiological studies have clearly identified that diabetes is a major factor for periodontitis, increasing the risk approximately three-fold compared to non-diabetic individuals, particularly if glycemic control is poor. This article discusses the possibility impact of diabetes on the periodontal patient and the ways in which untreated periodontitis may influence the course of diabetes. Diabetes mellitus is considered a risk factor and associated with an increased prevalence and severity of gingivitis and periodontitis. Inflammation plays an obvious role in periodontal diseases, evidence in literature also supports the role of inflammation as a major component in the pathogenesis of diabetes and diabetes complications. There is also evidence that periodontal disease can worsen a patient’s control of diabetes mellitus and proper management of periodontal disease can improve control of diabetes mellitus. The association between diabetes mellitus and periodontal diseases is clear that glycemic control improves periodontal conditions, while the management of periodontal infection improves glycemic control of diabetic patients (HbA1c reduction approximately 0,4%). Periodontal assessment is as important in people with diabetes as it is in people who do not have diabetes and people with diabetes should be made aware of their increased risk for periodontal disease.